A tripartite synapse model in Drosophila. - Rie Danjo (Public Library of Science (PLoS), 2011)
Tripartite (three-part) synapses are defined by physical and functional interactions of glia with pre- and post-synaptic elements. Although tripartite synapses are thought to be of widespread importance in neurological health and disease, we are only beginning to develop an understanding of glial contributions to synaptic function. In contrast to studies of neuronal mechanisms, a significant limitation has been the lack of an invertebrate genetic model system in which conserved mechanisms of tripartite synapse function may be examined through large-scale application of forward genetics and genome-wide genetic tools. Here we report a Drosophila tripartite synapse model which exhibits morphological and functional properties similar to those of mammalian synapses, including glial regulation of extracellular glutamate, synaptically-induced glial calcium transients and glial coupling of synapses with tracheal structures mediating gas exchange. In combination with classical and cell-type specific genetic approaches in Drosophila, this model is expected to provide new insights into the molecular and cellular mechanisms of tripartite synapse function.